Integrating Local Contents into Junior High School Student's English Learning Material - Yeni Nurmala Hidayati; Yudi Basuki (Universitas PGRI Madiun, 2021)
This study aimed at developing English local content material for seventh grade students of junior high school in SMPN 1 Trenggalek. Trenggalek local values were integrated into particular topics being addressed in the form of a textbook based on the 2013 curriculum. The data were gained through interview, observation and questionnaire. The result revealed that the locally – based developed material was successful to fulfill Trenggalek local content. For teacher, it was applied easily to achieve contextual learning and promote students’ interests. For students, it motivated them and their interest in learning English better and improved their ability to talk about their own area and environment.